Mechanical Behavior of Additively Manufactured Metallic Cellular Scaffold Structures for Bone Tissue Engineering - (:unkn) unknown (My University, 2021)
Critical-sized bone defects represent a significant challenge in the orthopedic field. Limitations on autograft and allograft as treatment techniques led researchers to explore the implantation of artificial bone tissue scaffolds. BTE scaffolds are three-dimensional cellular structures that provide mechanical support and behave like a template for bone tissue formation. Stress shielding in bones is defined as the bone weakening and reduction in bone density due to stiffness mismatch between the bone and the scaffold. This mismatch causes shielding of the bone by transferring stresses to the implant. The main motive of the research study is to address the stress shielding phenomenon as the main cause of bone resorption (loss), which leads to the eventual failure of bone implants—also, introducing a metal scaffold of viable stiffness and strength, which could serve as a replacement to the defective bone segment. The availability of additive manufacturing facilitated the fabrication of bone scaffolds with precise geometrical and structural configurations. This study aimed to reduce the stress shielding and introduce a cellular metal structure to replace defective bone by designing and manufacturing a numerically optimized stainless steel bone scaffold with an elastic modulus of 15 GPa that matches the structural modulus of the human cortical bone. Diagonal and cubic cell scaffold designs were explored. Strut and cell sizes were numerically optimized with a predetermined pore size to achieve the target cortical bone structural modulus. The optimized scaffold designs were manufactured using the laser powder bed fusion (LPBF) technique and experimentally tested in compression to validate the finite element analysis (FEA) model and explore the failure mechanisms of both scaffold designs. Scanning electron microscopy (SEM) was used to characterize the structural configuration of the manufactured scaffolds. Minimal porosity was found in struts, and variations in strut sizes were observed between the manufactured scaffolds and CAD models. In addition, rough surfaces were noticed due to the additive manufacturing process. The elastic modulus values obtained experimentally, as expected, were 1.6% and 4.7% lower than FEA results for the cubic and diagonal scaffolds, respectively, due to structural relative density variations in the scaffolds.Stretch-dominated failure was detected in the cubic scaffold, while bending-dominated failure was observed in the diagonal scaffold. The bending and torsional stiffnesses of both scaffold designs have been numerically evaluated. Higher bending and torsional moduli were observed in the diagonal scaffold than in the cubic scaffold. A three-point bending experiment was conducted to evaluate the bending properties of the scaffolds. The bending modulus of the cubic and diagonal scaffolds were experimentally investigated and found to agree with the numerical results. The diagonal scaffold's ultimate strain was significantly higher than the cubic scaffold; hence, the diagonal scaffold was substantially tougher with considerably higher energy absorption before fracture. Shear modulus was experimentally investigated and found to agree with numerical results. The shear modulus of the diagonal scaffold was observed to be significantly higher than the cubic scaffold. The effect of varying the porosity of the scaffolds on the elastic properties was investigated, and relationships were developed. Finally, a comparison of the mechanical properties of the studied BTE scaffolds with the cortical bone properties under longitudinal and transverse loading was presented. Future work includes investigating the fatigue strength and comparing the behavior of cubic and diagonal scaffold designs under cyclic loading. The study presented the design and manufacturing of BTE scaffolds with mechanical properties comparable to cortical bone mechanical properties. The study also produced an innovative metal cellular structure that can replace large bone segments anywhere in the human body.